A pátria de chuteiras: um estudo da produção de sentido da marca Nike no Brasil - Casanova Junior, Carlos (2013)
This dissertation investigates how the personalities endorse the Nike brand represented through the commercials aired in two World Cups in 1994 and 2010. It is a semiotic study of advertising films presented by the organization on the eve of the world championships. Our objectives were to analyze the advertising signs used to represent, translate and sensitize the audience around the brand and the representations of football. For this, we analyze the characteristics of verbal and visual, in order to identify the common elements, ie, images, messages , calls , as well as ideas , values and cultural symptoms that materialize on the ads and provide symbolic exchanges with its consumers . For the enrichment of semiotic analysis, we set up two discussion groups for deepening issues related brand and football. With the two new groups emerged and questions, for this reason, we had to incorporate lines of semiotics in order to answer the questions that were posed. Thus, we seek contributions of Perez, Lancaster and Corte- Real, a source to elucidate the issues related to the brand, aimed at mapping occurs as building emotional ties and affective functions that go beyond identity and differentiation proposals, in principle, to the brand. And supplemental path analysis was incorporated psychoanalytic semiotics to deepen the consumer's relationship with the brand. The dissertation begins with a literature search related to football, especially the presence of Brazil in World Cups. This study aims to analyze how the tournaments are received by the audience and how they leverage communication of brand sporting goods. Following a chapter mark sought to discuss their role, party from its origin to the concepts of brand postmodern described by Semprini